Assessing the microbial community dynamics and the role of bacteriophages in bacterial mortality in Lake Geneva - Duhamel, Solange; Domaizon-Pialat, Isabelle; Personnic, Sébastien; Jacquet, Stéphan (Revue des sciences de l'eau / Journal of Water Science)

(untitled) (Université du Québec - INRS-Eau, Terre et Environnement (INRS-ETE), 2006)
SummaryThe aims of this work were to study, for the first time, the succession of microbial communities (from viruses to ciliates) in the largest occidental European lake (Lake Geneva) and to perform two one-week in situ experiments in March-April (Exp1) and May (Exp2) 2004 in order to assess both small flagellate protozoan and virus-induced mortality of heterotrophic bacteria. Both nanoflagellates and viruses could be responsible for 31 to 42% of the total daily mortality of heterotrophic bacteria. In May (Exp2), viruses could explain up to 10% of the bacterial mortality whereas flagellates were responsible for 32% of the bacterioplankton removal. These results provide new evidence for the critical role played by viruses in the functioning of the microbial food webs and highlight the importance of further considering this biological compartment for a better understanding of the plankton ecology of Lake Geneva.